Assessment of inequalities in women’s and children’s health: Why, how, and for whom? Analyses of the Brazilian Live Birth Information System. - Fernando César Wehrmeister; Janaína Calu Costa; Luiza Eunice Sá da Silva; Natalia Peixoto Lima; Francine dos Santos Costa; Aluísio Jardim Dornellas de Barros (Revista Brasileira de Epidemiologia)
ABSTRACT In this manuscript we discuss the importance of monitoring the analyses on health inequalities in women’s and children’s health. Data from the Brazilian Live Birth Information System were used to introduce the main inequality measures. The years from 2020 to 2022 were combined and at least one and eight or more antenatal care visits were considered as outcomes. As inequality measures, simple (ratios and differences) and complex measures for ordered (slope index of inequality and concentration index) and unordered (weighted and unweighted mean absolute difference from the mean) outcomes were presented. We discuss the strengths, limitations, and importance of inequality monitoring for researchers and policymakers.